Burning mouth syndrome: A comparative cross-sectional study - Maryam Rabiei; Ehsan Kazemnezhad Leili; Leili Alizadeh (Contemporary Clinical Dentistry, 2018)
Background and Aim: Burning mouth syndrome (BMS) may be defined as a burning sensation in the oral mucosa usually unaccompanied by clinical signs. Multiple conditions have been attributed to a burning sensation. The aim of this study was to determine the role of age and sex in BMS. Materials and Methods: A total of 195 consecutive patients with BMS and 95 healthy patients without burning sensation were recruited in this study. Patients with BMS had experienced oral, burning sensations for at least 6 months without oral clinical signs, and with a normal blood count. Multiple logistic regression analyses were utilized to define the main predictors. Results: Menopause, candidiasis, psychological disorders, job status, denture, and dry mouth were significantly frequent in BMS patients. Multivariate logistic regression indicated age (odds ratio (OR) =1.12, 95% confidence interval (CI): 1.08–1.15, P < 0.0001) and sex (OR = 3.14, 95% CI: 1.4–6.7, P < 0.002) significantly increase the odds of BMS. Psychological disorders (OR = 3.39, 95% CI: 1.2–9.5, P < 0.02) and candidiasis remain as predictive factors. Ultimately, age was defined as a critical predictor. Moreover, we can therefore predict that a 60-year-old woman with psychological disorders is 25 times more likely to suffer from BMS than a man 10 years younger who has no psychological disorder. Conclusion: Age and sex were the main predictors in BMS. Psychological disorders and candidiasis were significantly associated with the occurrence of BMS.